The Management of the Bus Rapid Transit (BRT) System and Its Impact on Mobility in Lagos State, Nigeria - Lasisi, Olukayode; Obembe, Mayowa Paul; Onabanjo, Leke Kayode; Bamiro, Tolulope Oluwatosin; Iyiola, Oluwatobee Omowumi (UI Scholars Hub, 2025)
Lagos is famous for its high traffic congestion and insufficient road infrastructure. This study examined the effect of BRT management and its influence on mobility in Lagos State. The study adopted a cross-sectional design involving data gathering through the primary data collection method using a closed-ended questionnaire purposively administered to 100 commuters of BRT buses in Lagos. The findings revealed a high positive relationship between managing the BRT system and mobility in Lagos State. Additionally, the findings indicate a robust and positive causal relationship between Lagos State’s BRT system and transportation development. The BRT system contributes to improving transportation infrastructure and other related aspects within Lagos State, and this relationship is statistically significant. With p < 0.05, the relationship is not due to chance. However, the findings revealed that the inaccessibility of BRT buses, insecurity at the BRT stations, and the inability to integrate the BRT service with other transportation systems were the major constraints that bedevilled the BRT project in easing the mobility of Lagos residents. The study concluded that the BRT system management contributed significantly to Lagos State’s transportation development. This study recommended that Lagos should adopt a thorough and well-rounded transportation strategy that views the BRT network as a component of a wider network that includes buses, mini-buses, ferries, and other forms of transit.